New Geometries for Calix[6]arene‐Based Rotaxanes. Issue 21 (28th March 2019) - Bazzoni, Margherita; Zanichelli, Valeria; Casimiro, Lorenzo; Massera, Chiara; Credi, Alberto; Secchi, Andrea; Silvi, Serena; Arduini, Arturo
Abstract : Understanding the role played by the nature, number, and arrangement of binding sites anchored to a macrocycle remains a topic of current interest for the synthesis of new interwoven species. We report the synthesis and detailed structural characterization of a new calix[6]arene derivative decorated with two phenylureido groups anchored at the diametrical position of the calix upper rim that adopts a 1, 2, 3‐alternate conformation in solution and in the solid state. Preliminary data on the ability of this host to form redox‐active pseudorotaxanes and rotaxanes are reported. Abstract : A bis( N‐ phenylureido)calix[6]arene that adopts a 1, 2, 3‐alternate conformation has been synthesized, and its structure has been established in solution of low polarity solvents and in the solid state. Its ability to act as a wheel and form interwoven systems with viologen salts was studied through structural characterization and electrochemical measurements.